Metaphor Windows and Mirror Technique in Cooperative Games for Develop Emotional Literacy on Children - Galang Surya Gumilang (Universitas Muhammadiyah Metro, 2017)
This article examines and discusses (1) the concept of emotional literacy, (2) the concept of the child and his emotions, (3) the metaphor of windows and mirrors in a cooperative game, (4) metaphor window and mirror technique in cooperative games for develop emotional literacy on children. Emotional literacy means the ability to recognize, understand, and realize the emotional self, labeling emotions felt, expressing emotions and situations experienced by way of an appropriate and proper emotional management. Using the metaphor of the window and the mirror technique, students can understand his emotions as well as others. Cooperative games used to stimulate emotions and express and reflect the positive emotions that exist in children.